External validation of the GRACE risk score and the risk–treatment paradox in patients with acute coronary syndrome. Issue 1 (30th March 2022) - van der Sangen, Niels M R; Azzahhafi, Jaouad; Chan Pin Yin, Dean R P P; Peper, Joyce; Rayhi, Senna; Walhout, Ronald J; Tjon Joe Gin, Melvyn; Nicastia, Deborah M; Langerveld, Jorina; Vlachojannis, Georgios J; van Bommel, Rutger J; Appelman, Yolande; et al.
Abstract : Objectives: To validate the Global Registry of Acute Coronary Events (GRACE) risk score and examine the extent and impact of the risk–treatment paradox in contemporary patients with acute coronary syndrome (ACS). Methods: Data from 5015 patients with ACS enrolled in the FORCE-ACS registry between January 2015 and December 2019 were used for model validation. The performance of the GRACE risk score for predicting in-hospital and 1-year mortality was evaluated based on indices of model discrimination and calibration. Differences in the delivery of guideline-recommended care among patients who survived hospitalisation (n=4911) per GRACE risk stratum were assessed and the association with postdischarge mortality was examined. Results: Discriminative power of the GRACE risk score was good for predicting in-hospital (c-statistic: 0.86; 95% CI: 0.83 to 0.90) and 1-year mortality (c-statistic: 0.82; 95% CI: 0.79 to 0.84). However, the GRACE risk score overestimated the absolute in-hospital and 1-year mortality risk (Hosmer-Lemeshow goodness-of-fit test p<0.01). Intermediate-risk and high-risk patients were 12% and 29% less likely to receive optimal guideline-recommended care compared with low-risk patients, respectively. Optimal guideline-recommended care was associated with lower mortality in intermediate- and high-risk patients. Conclusions: The GRACE risk score identified patients at higher risk for in-hospital and 1-year mortality, but overestimated absolute risk levels in contemporary patients. Optimal guideline-recommended care was associated with lower mortality in intermediate-risk and high-risk patients, but was less likely to be delivered with increasing mortality risk.